The Role of Social Media as a Learning Medium In Developing 21st-Century Skills among Students - Annisa Mardiah; Fauziah Syania Asri; Putri Intan Syamsudin; Rafi Sulthan; Fajar Al Kautsar; Anjar Sulistiyani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
The development of information and communication technology has brought significant changes to education, particularly in the use of social media as a learning medium. Twenty-first-century learners, who belong to the digital generation, are often familiar with social media platforms such as YouTube, TikTok, WhatsApp, and Instagram. This condition creates substantial opportunities for the education sector to integrate social media into the learning process to develop 21st-century skills, including critical thinking, creativity, communication, collaboration, and digital literacy. This study aims to examine the role of social media as a learning medium in developing 21st-century skills among students. The research employs a descriptive qualitative approach using a literature review (library research) method. Data were obtained through the examination of various literature sources, including national and international scientific journal articles, reference books, and relevant educational policy documents. Data analysis was conducted using content analysis techniques, encompassing data reduction, data presentation, and conclusion drawing. The findings indicate that the appropriate and well-directed use of social media can enhance student engagement in learning and support the development of 21st-century skills. Nevertheless, the role of educators is essential in designing structured learning activities, providing guidance, and fostering digital literacy so that social media can be utilized optimally and responsibly within the educational context.